Cytochrome P450 drug metabolism and protein induction and inhibition in fish liver microsomes - Smith, Emily M. (My University, 2009)
The emergence of pharmaceuticals in wastewater effluent is of increasing concern to aquatic organisms. Cytochrome P450s (CYPs) are important pharmaceutical and xenobiotic-metabolizing proteins, and their functions are well studied and understood in mammals. However, studies on CYP function and modulation in non-mammalian vertebrate systems are much less defined, and function is often inferred from mammalian data, assuming similar function across vertebrate taxa. In this study, we investigate in vivo induction and in vitro metabolism and inhibition of CYPs in fish liver microsomes.
In this thesis, a number of fluorometric CYP-catalyzed assays and fluoxetine, a model selective serotonin reuptake inhibitor (SSRI) , have been used to assess CYP mediated metabolism in fish. Overall, we raise questions about extrapolating known mammalian data to fish CYP function. Fluoxetine, a CYP2D6 substrate in humans, was not metabolized well in fish liver. These data suggest that perhaps fish produce a fluoxetine metabolite that is not produced by mammals. We investigate the basal metabolism and induction potential for hepatic CYPs in two fish species, rainbow trout (Oncorhynchus mykiss) and killifish (Fundulus heteroclitus). Species differences were found in the baseline metabolism of these substrates. Treatment with known mammalian CYP inducers, dexamethasone (DEX) , pregnenolone-16α-carbonitrile (PCN) , and rifampicin (RIP) did not cause broad, measurable CYP induction in either fish species. β-naphthoflavone (BNF) , a prototypical CYPIA inducer, showed significantly induced activity across many substrates, providing evidence that BNF induces more broadly than expected. We also assess the inhibition potential of potent inhibitors of important drug metabolizing CYPs in mammals: fluoxetine, ciprofloxacin, gemfibrozil and erythromycin. These compounds produce significant inhibition over most substrates tested, and are not substrate-selective as would be predicted by their inhibitions in mammals.
The experiments carried out within this thesis add to our knowledge of functional characterization of CYP induction, inhibition and metabolic activity in fish. Using a comparative approach, a number of fish species were tested for in vitro catalytic function of these contaminant-metabolizing proteins and provide evidence that fish CYPs respond differently to inducing and inhibitory compounds compared to mammals. Extrapolation across taxa should be carefully considered before assuming similar function.
Keywords: Biology; Biology